Change of Direction Asymmetry in Youth Elite Tennis Players: A Longitudinal Study - D’Hondt, Joachim; Chapelle, Laurent (International Journal of Sports Medicine, 2024)
Longitudinal investigations into the development of inter-limb asymmetry in sports are scarce. This study examined the development of change of direction (COD) asymmetry magnitude in youth elite tennis players. Dominant (overall best performance) and non-dominant (best performance on the other side) scores and COD asymmetry magnitude were quantified annually (up to six years) in 323 male and 235 female players (ages 6 to13 years). Linear mixed effects regression models examined the development of COD performance and asymmetry magnitude according to players’ chronological age and sex. Kappa coefficients examined the consistency for the direction of asymmetry across test occasions. Regardless of sex, COD performance significantly improved (p<0.001) while COD asymmetry magnitude significantly decreased (− 0.17±0.87% / year) with increasing chronological age. Regardless of age, males showed significantly lower COD times (− 0.111±0.091 s) and lower COD asymmetry magnitude (− 0.30±1.00%) compared to females. The slight and poor (k-value=0.02–0.00) kappa coefficients for males and females, respectively, highlight the direction specificity of functional asymmetry. These data show that whereas performance of the COD test improved, the magnitude of COD asymmetry declined across chronological age in youth tennis players.
Keywords: interlimb; physical performance; youth athletes; unilateral; monitoring; racquet sports